2013
DOI: 10.1177/004005991304500404
|View full text |Cite
|
Sign up to set email alerts
|

Using an iPad in Inclusive Preschool Classrooms to Introduce STEM Concepts

Abstract: Ms. Christa is a preschool teacher in an inclusive mixed-ability classroomand is leading a small group activity with four students. Kolby, a 4-year-old identified with a pervasive development disorder not otherwise specified (PDD-NOS), is sitting beside her as she introduces him to a new learning activity with the iPad. His peers wait for their turn on the iPad as she introduces Monkey Math, one of several science, technology, engineering, and mathematics (STEM) apps available on the classroom's iPad. Across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 6 publications
4
68
0
11
Order By: Relevance
“…The severity of the performances for students with disabilities is even greater when compared to their peers. While comparing international scores of students with disabilities is virtually impossible due to varying definitions for determining disability, nationally, students with disabilities perform significantly lower than their peers without disabilities (Aronin & Floyd, 2013;Basham & Marino, 2013;National Center for Education Statistics, 2013).…”
Section: What Is Stem?mentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of the performances for students with disabilities is even greater when compared to their peers. While comparing international scores of students with disabilities is virtually impossible due to varying definitions for determining disability, nationally, students with disabilities perform significantly lower than their peers without disabilities (Aronin & Floyd, 2013;Basham & Marino, 2013;National Center for Education Statistics, 2013).…”
Section: What Is Stem?mentioning
confidence: 99%
“…Some researchers have referred to STEM education as a broad education category involving math, science, engineering, or technology education; thus, teaching any one of the four disciplines can simply be referred to as STEM education (Cotabish, Dailey, Robinson, & Hughes, 2013;Watt, Therrien, Kaldenberg, & Taylor, 2013). Others consider STEM education to be the use of technology as a part of the instructional tools (e.g., iPad, pc) used in education (Aronin & Floyd, 2013). These perspectives consider STEM to be simply an acronym for grouping four disciplines without any relationship among four interwoven domains.…”
Section: Educational Perspectives On Stem: Interdisciplinary Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Toledo and Mattoon (2012), it was revealed that tablets reinforce children to work cooperatively in the classroom, increase creativity and communication skills among children. Tablets, which can be used as new material in classrooms, are presented to small and big groups of students with the guidance of teachers (Aronin & Floyd, 2013), thus tablet use is practiced under the control of teachers. In preschools, tablets can be integrated into the curriculum due to its facilitative effects on learning through various applications Aronin & Floyd, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tablets, which can be used as new material in classrooms, are presented to small and big groups of students with the guidance of teachers (Aronin & Floyd, 2013), thus tablet use is practiced under the control of teachers. In preschools, tablets can be integrated into the curriculum due to its facilitative effects on learning through various applications Aronin & Floyd, 2013). Herein, it can be concluded that when under the control of teachers and in accordance with the program, tablet use in preschools can be an effective teaching tool (Couse & Chen, 2010;McPake, Plowman, & Stephen, 2013;Shifflet, Toledo, & Mattoon, 2012).…”
Section: Introductionmentioning
confidence: 99%